2023
DOI: 10.1007/s40121-023-00845-7
|View full text |Cite
|
Sign up to set email alerts
|

Is Azvudine Comparable to Nirmatrelvir-Ritonavir in Real-World Efficacy and Safety for Hospitalized Patients with COVID-19? A Retrospective Cohort Study

Qinqin Zhao,
Bei Zheng,
Bing Han
et al.

Abstract: Introduction Azvudine and nirmatrelvir-ritonavir are more extensively used to treat COVID-19 in China due to their earlier approval by the National Medical Products Administration. However, there has been a scarcity of research directly comparing the clinical outcomes between azvudine and nirmatrelvir-ritonavir till now. We aimed to make a head-to-head comparison of the efficacy and safety of azvudine or nirmatrelvir-ritonavir in hospitalized patients with COVID-19 in China. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Similar to Gao et al, 11 the confounding factors in the laboratory test results was balanced in our study to ensure the greatest possible reliability of the findings. Consistent with our study's results, studies by Zhao Q et al 32 and Zhao X et al 33 also found that there was no significant difference in overall mortality between the nirmatrelvir/ritonavir and azvudine groups. However, Dian et al 12 found that among patients with COVID-19 and comorbidities, the risk of composite disease progression was lower in the azvudine group than in the nirmatrelvir/ ritonavir group.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to Gao et al, 11 the confounding factors in the laboratory test results was balanced in our study to ensure the greatest possible reliability of the findings. Consistent with our study's results, studies by Zhao Q et al 32 and Zhao X et al 33 also found that there was no significant difference in overall mortality between the nirmatrelvir/ritonavir and azvudine groups. However, Dian et al 12 found that among patients with COVID-19 and comorbidities, the risk of composite disease progression was lower in the azvudine group than in the nirmatrelvir/ ritonavir group.…”
Section: Discussionsupporting
confidence: 92%
“…However, inconsistent results are found among different studies regarding the impact of azvudine on all-cause mortality [ 17 , 37 39 ]. Nonetheless, there are promising results showing that there was no difference in mortality between COVID-19 patients using Paxlovid and those using azvudine, which was a consistent finding in two retrospective cohort studies [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 58%
“…The pooled estimate of nine studies [ 19 , 20 , 27 29 , 32 , 33 , 37 , 38 ] showed a significant difference in mortality rate between patients receiving azvudine and SOC (RR = 0.48, 95% CI: 0.40 to 0.57, P < 0.001, I 2 = 0%, GRADE certainty: moderate) ( Fig 2 ). According to the pooled estimate, seven studies [ 6 , 7 , 25 , 32 , 35 – 37 ] revealed a significant difference in mortality rate between the azvudine and nirmatrelvir-ritonavir groups (RR = 0.73, 95% CI: 0.58 to 0.92, P < 0.05, I 2 = 41%, GRADE certainty: moderate) ( Fig 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled estimate of four papers [ 8 , 13 , 27 , 30 ], showed a significant difference in negative PCR conversion time between the azvudine and SOC/PBO groups (SMD = - 0.75, 95% CI: -1.29, - 0.21; P < 0.05, I 2 = 75%, GRADE certainty: low) ( Fig 4 ). The pooled estimate of three papers [ 14 , 35 , 36 ] highlighted no significant differences between the azvudine and nirmatrelvir-ritonavir groups concerning negative PCR conversion time (SMD = 2.14, 95% CI: -1.08, 5.36; P = 0.19, I 2 = 99%, GRADE certainty: low) ( Fig 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation